Eco - Cultura: el organismo y la máquina (2020)
Eco-culture is a project that encompasses all the dynamics capable of creating multiple activities for the integral growth of the human being that once incorporates and respects the living organism in the place where they are developed. Ecoculture expands and sustainably improves existing resources and sociocultural practices that benefit all organisms. This is how the organism is in the center of the structure and this is the determining factor for architectural design. Thus, for the terms of this project, the organism is understood as every natural living being capable of coexisting with its environment over time and which grows continuously under the indicated opportunities. On the contrary, the machine is defined as any artificial element created by man and with a mission for its own benefit within a specific place. Therefore, this project seeks the recovery and protagonism of the native organisms of the Sabana Station hidden by the masonry barrier, which generates a gray and polluted atmosphere where the machine predominates over the organism. Through the improvement towards the sustainability of the link found between nature, the machine and the individual, it seeks to attract not only the community that surrounds the area but also the different species (flora and fauna) that at some point could have inhabit and can now coexist with the inhabitants and their practices within the project area. Therefore, it is a sustainable architecture that creates an optimal habitat for the integration of the organism, the machine and the individual within the railway route from the Estación de la Sabana to the Plaza de Mercado de Paloquemao.